MANAGEMENT OF LARGE SIZE AND MULTIPLE BENIGN BREAST LESIONS USING ONCOPLASTIC SURGICAL SKILLS - Saira Saleem; Farhan Javed; Irshad Ahmad, (Malaysian Journal of Medical Research (MJMR), 2020)
Objective: Management of multiple and large size benign breast lesions is challenging. Usual excision techniques are associated with unacceptable breast deformity in such cases. However, these can effectively be managed with minimum breast deformity using oncoplastic skills used for breast cancer. Our objective was to evaluate the oncological outcome and patient satisfaction of managing large and multiple benign breast lesions using oncoplastic surgical skills. Methods: This was a descriptive, prospective study conducted in department of Surgery, Madina Teaching Hospital, Faisalabad, Pakistan from January 2018 to December 2019. Females with age range of 12 to 60 years were included in the study. Different oncoplastic techniques were used depending on location and size of tumour as well as size and degree of breast ptosis.Main outcome measures were tumour recurrence and patient satisfaction with the cosmetic outcome. Results: Twenty-eight female patients with large size (>5cm) or multiple benign breast tumors were managed.Most common techniques used were round block mammoplasty and wise pattern reduction mammoplasty. Giant fibroadenoma (35.7%), benign phyllodestumour (14%) and ductal hyperplasia (usual 10.7% & atypical 7%) were the most common histological findings. No tumour recurrence was seen during our study period and minimum scarring and no breast deformity in these cases, gained high patient satisfaction. Conclusion: Oncoplastic skills achievefavourable aesthetic and oncological results for large and multiple benign breast tumours.